Centralidades e novas áreas centrais em Campina Grande-PB: o centro do bairro das Malvinas - Oliveira, Taynan Araújo de (2017)
This work aims to understand how the increase and diversification of commercial establishments conditions the conformation of new central areas in the urban structure of Campina Grande - PB. In the course of the research, we will analyze different forms of Expression of Centrality, we will understood as such, from the relationships and the flows constituted. In this way, we will start from the assumption that Centrality produces and structures itself in the urban space itself. In this sense, we will examine and to discuss important concepts in this process, such as: Center, Decentralization, New Central Areas, Urban and City Restructuring, Subcenter and Neighborhood Center. Although, each one is composed as concepts studied for a long time, we will present the relevant differences, especially those evidenced by the Subcenter and the Neighborhood Center; As well as, the pattern of structuring in a Middle City. In order to analyze the distribution and concentration of commercial establishments in the urban structure of Campina Grande, it became, therefore, important to discuss and to analyze the National Register of Addresses and Statistical Purposes – CNEFE, and the National Register of Economic Activities - CNAE data’s, both Present in the Brazilian Institute of Geography and Statistics - IBGE, in addition to forms, interviews, field surveys and mappings, based on the use of Arcgis Software. Finally, in the face of current transformations and through the structuring and restructuring process, the value of other spaces/areas of the city, which concentrate commercial and service establishments, Minimum spatial reach. In view of this, it is, undoubtedly, important to consider that the Center is the main commercial matrix; However, this does not negate the existence of other spaces that exercise the same central function, in other levels; As an example, we highlight the Malvinas Neighborhood Center, the main object of this research. Consequently, we have a conclusion that the said area is constituted as a Neighborhood Center due to its pattern of structuring, organization and to consolidate itself with a minimal central range extension. In addition, it presents the potential for conformation of a Subcenter, due to the installation of public services that extend the centrality to the maximum reach level, as well as, increase and diversification of the commercial branches.